1999
DOI: 10.1088/0953-4075/32/14/321
|View full text |Cite
|
Sign up to set email alerts
|

On a heating mechanism for cold hydrogen and deuterium atoms produced at the edge of a tokamak plasma

Abstract: Spectroscopic measurements of the D α and H α line profiles emitted within the edge region of a tokamak plasma, have revealed the existence of a cold central component, broadened mainly by the Zeeman effect arising from the confining magnetic field. Evaluation of the Doppler broadening suggests that the cold component is probably produced by electron impact-induced molecular dissociation, dissociative excitation being one of the few mechanisms which can explain the formation of atoms of kinetic energy around 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
135
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(142 citation statements)
references
References 34 publications
(72 reference statements)
6
135
1
Order By: Relevance
“…͑18 and 30 allowed, 2 and 4 ⌬J forbidden͒. [5][6][7] The corresponding perturbed line strengths are calculated according to the method described in Ref. 23.…”
Section: Analysis Of the Zeeman Profiles And Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…͑18 and 30 allowed, 2 and 4 ⌬J forbidden͒. [5][6][7] The corresponding perturbed line strengths are calculated according to the method described in Ref. 23.…”
Section: Analysis Of the Zeeman Profiles And Discussionmentioning
confidence: 99%
“…1,2 Its quantitative estimate is required for the purpose of evaluating the particle fueling rate and controling the recycling neutrals in the long pulse discharge operation. 3,4 Information on neutral atoms has been obtained from spectroscopic measurements of the Zeeman ͑Paschen-Back͒ split profiles of lines emitted from the divertor or the periphery region in TEXTOR ͑Tokamak-Experiment for Technology Oriented Research͒, [5][6][7][8] JT-60U ͑Japan atomic energy research institute Tokamak-60 Upgrade͒, 9,10 Alcator C-Mod, [11][12][13] Doublet III-D, [14][15][16] ASDEX-U ͑Axially Symmetric Divertor Experiment Upgrade͒, 17,18 Tore Supra, 19,20 TRIAM-1M ͑Torus of Research Institute for Applied Mechanics͒ ͑Ref. 21͒ for hydrogen/deuterium, and in LHD ͑Large Helical Device͒ for helium.…”
Section: Introductionmentioning
confidence: 99%
“…͑2͒ the H Ϫ on their way to center can be cooled by excited argon atoms by the mechanism analogous to the one described in Ref. 8. The authors of Ref.…”
Section: B Negative Ion Population Fractionsmentioning
confidence: 96%
“…The authors of Ref. 8 showed that the heating of excited (nϭ3) hydrogen atoms by a hot deuteron background is ϳ10 times more effective than the heating of the atoms in ground state. In other words, the heat transfer between an excited atom and a hot background is much more effective than for the atom in ground state.…”
Section: B Negative Ion Population Fractionsmentioning
confidence: 99%
“…So for instance, it is an established fact that the Zeeman effect, or more precisely the Paschen-Back effect, dominates the fine-structure splitting of the Balmer-α line emission at the plasma edge of fusion devices 27 . In case of Maxwellian distribution function of atoms every magnetic component of the spectral line is described using a Doppler profile taking into account the different source of excited atoms 27,28 . In the case of MSE measurements the emissions takes place predominantly in the static crossed electric and magnetic fields, being a subject of studies for high Rydberg states 26,29 .…”
Section: Atomic Model Of the Zeeman-stark Multipletmentioning
confidence: 99%